Normal breast parenchyma: contrast enhancement kinetics at dynamic MR mammography--influence of anthropometric measures and menopausal status - Hegenscheid, Katrin; Schmidt, Carsten O; Seipel, Rebecca; Laqua, René; Ohlinger, Ralf; Kühn, Jens-Peter; Hosten, Norbert; Puls, Ralf (Radiology, 2013)
To study T1 baseline signal intensity (SI) and contrast material enhancement kinetics of normal breast parenchyma by using dynamic contrast-enhanced (DCE) magnetic resonance (MR) mammography and to determine the influence of anthropometric measures and menopausal status on the variability of these features. Institutional review board approval and written informed consent were obtained. Between June 2008 and September 2011, 345 women (age range, 26-81 years; mean age, 51.3 years ± 11.6 [standard deviation]) underwent DCE MR mammography, with T1-weighted three-dimensional MR images (repetition time msec/echo time msec, 8.86/4.51; flip angle, 25°) acquired with a 1.5-T whole-body MR unit before and 1, 2, 3, 4, and 5 minutes after a gadobutrol bolus injection of 0.1 mmol per kilogram of body weight. Regions of interest were traced manually, and T1 SI of parenchyma was recorded. The influence of different predictors of T1 baseline SI and contrast enhancement was studied by using random-effects models. T1 baseline SI varied considerably between women, with a mean of 167.7 ± 49.2 (71.4-424.7 [range]) and 175.9 ± 48.9 (51.8-458.3) in the right and the left breast, respectively (P < .01). T1 baseline SI increased linearly with age (P < .0001) and body weight (P < .0001). After contrast material delivery, relative percentage of enhancement was 8.1%, 13.8%, 18.2%, 22.1%, and 24.6% at 1, 2, 3, 4, and 5 minutes, respectively, but varied considerably between women. Contrast enhancement was 9.3% in the lowest quintile and 47.4% in the highest. Contrast enhancement increased with body weight (P < .01) but decreased in postmenopausal women (P < .01). Women with higher baseline T1 SI tended to have a higher contrast enhancement slope. Anthropometric measures and menopausal status contribute to a large variability in contrast enhancement of normal breast parenchyma. This might influence the interpretation of contrast enhancement kinetics of breast lesions and current strategies for determining contrast medium dose for breast MR imaging.